A flow analysis and preemption framework for periodic traffic in an SDN network. (31st May 2018) - Bull, Peter; Murphy, Stephen; Bruno Junior, Nelson; Austin, Ron; Sharma, Mak
Summary: Software Defined Networking (SDN) utilises the concept of centralised command and control to significantly improve network manageability. However, this is at the expense of performance, with the controller(s) now being a bottleneck. This paper further develops the authors' concept of using a Preemptive Flow Installation Mechanism (PFIM) to improve SDN performance for periodic traffic by limiting the number of controller look‐ups through predicting when a flow is likely to need a particular rule. Unlike previous work in this area, the paper uses real SDN hardware and a series of experiments containing varying amounts of temporally predictable and random flows, along with a modified version of the POX controller. The work goes on to discuss issues found pairing the controller with hardware, before presenting results that demonstrate that the system can detect majority of temporally periodic flows and preemptively install a flow rule, facilitating the performance comparable to layer two switching speeds. The paper also suggests that the performance of the modified controller is approximately equivalent to the unmodified version when dealing with non‐periodic traffic.